The Neural Basis of Herding Decisions in Enterprise Clustering: An Event-Related Potential Study - Zhang, Wuke; Yang, Danping; Jin, Jia; Diao, Liuting; Ma, Qingguo (Frontiers in Neuroscience, 2019)
Herding behavior refers to the social phenomenon in which people are intensely influenced by decisions and behaviors of others in the same group. Even though several recent studies have explored the neural basis of herding decisions in people’s daily life (e.g., consumption decision), the neural processing of herding decisions in enterprise behavior is still unclear. To address this issue, this study extracted the event-related potentials (ERPs) from electroencephalographic data when participants (i.e., top executives in real enterprises) performed a choice task in which they should judge whether to let their enterprises settle in an industrial zone when the occupancy rate of the industrial zone is low or high. The behavioral results showed that participants elicited a higher acceptance rate in the high occupancy rate condition than the low one, suggesting the existence of herding tendency in top executives’ business decisions. The ERPs results indicated that anticonformity choices induced a larger N2 amplitude compared to herding choices, demonstrating that participants may experience greater perceived risk and higher decisional conflicts when they made anticonformity choices. In contrast, we observed that herding choices induced a larger LPP amplitude relative to anticonformity choices, hinting that participants may experience better evaluation categorization and greater decision confidence when they made herding choices. Based on these results, this study provides new insights into the neural basis of top executives’ herding decisions in business behavior.